Disruption, but not overexpression of urate oxidase alters susceptibility to pentylenetetrazole‐ and pilocarpine‐induced seizures in mice. (9th May 2016) - Thyrion, Lisa; Portelli, Jeanelle; Raedt, Robrecht; Glorieux, Griet; Larsen, Lars E.; Sprengers, Mathieu; Van Lysebettens, Wouter; Carrette, Evelien; Delbeke, Jean; Vonck, Kristl; Boon, Paul
Summary: There is a continuous drive to find new, improved therapies that have a different mechanism of action in order to help diminish the sizable percentage of persons with pharmacoresistant epilepsy. Uric acid is increasingly recognized as contributing to the pathophysiology of multiple disorders, and there are indications that uric acid might play a role in epileptic mechanisms. Nevertheless, studies that directly investigate its involvement are lacking. In this study we assessed the susceptibility to pentylenetetrazole‐ and pilocarpine‐induced seizures in mice with genetically altered uric acid levels by targeting urate oxidase, which is the enzyme responsible for uric acid breakdown. We found that although disruption of urate oxidase resulted in a decreased susceptibility to all behavioral end points in both seizure models, overexpression did not result in any alterations when compared to their wild‐type littermates. Our results suggest that a chronic increase in uric acid levels may result in decreased brain excitability.